The marriage of opposites [large type] : a novel - Hoffman, Alice (Center Point Large Print, 2015)
"A forbidden love story set on the tropical island of St. Thomas about the extraordinary woman who gave birth to painter Camille Pissarro, the Father of Impressionism"--